"There is no carnival without samba": Revealing barriers hampering biodiversity-based R&D and eco-design in Brazil. (15th January 2018) - Jabbour, Charbel Jose Chiappetta; Jugend, Daniel; Jabbour, Ana Beatriz Lopes de Sousa; Govindan, Kannan; Kannan, Devika; Leal Filho, Walter
Abstract: Considering the unique relevance of Brazilian biodiversity, this research aims to investigate the main barriers to biodiversity-based R&D and eco-design development in a leading national company which has been commended for its innovation and sustainability. The methodology for this research was based on on-location visits, in-depth interviews, and consensus building among R&D, sustainability, and quality managers. A multi-criteria decision-making (MCDM) approach was adopted through interpretive structural modelling (ISM), a method that assists decision makers to transform complex models with unclear data into structural models. Some of the most influential barriers to biodiversity-based eco-design initiatives are "lack of legal incentive", "not enough demand from the market", and "not enough available knowledge/scientific data." The most relevant barrier was "no legal incentive" from government. Consequently, managers should concentrate their efforts in tackling those barriers that may affect other barriers known as 'key barriers'. Government should work decisively toward promoting a framework of legal incentives for bio-based eco-design; otherwise, metaphorically, "there is not carnival without the samba singer who pushes the rhythm". The results given here reveal the barriers for bio-based eco-design in a Brazilian leading company, and this is the first work combining ISM to barriers to biodiversity R&D and eco-design. Highlights: Barriers to biodiversity-based eco-design in a leading Brazilian company were analyzed. A multi-criteria decision making (MCDM) approach was adopted as research methodology. It was discovered that lack of "legal incentives" was the most influential barrier. Other relevant barriers were discussed, such as: not enough demand from the market and not enough available knowledge. This is the first paper combining ISM to barriers to biodiversity R&D and eco-design.